PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP LUAS PENGUNGKAPAN SUKARELA DAN IMPLIKASINYA TERHADAP BIAYA MODAL EKUITAS (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Tahun 2011) - Dinda Putri Oktaviani Setyaningrum; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2013)
This study aims to obtain empirical evidence about the influence of the firm characteristics to extensive voluntary disclosure and its implications for the cost of equity capital. The study is divided into two models. The first model examined the influence of the firm characteristics to extensive voluntary disclosure. In the first model, the firm characteristics are represented by six variables. The second model examined the effect of extensive voluntary disclosure to the cost of equity capital.Sample of this study is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2011. The data were collected by purposive sampling method. Data analysis tool used is regression analysis. Multiple regression is used to test the first model and for the second model used linear regression.The results of this study indicate that the firm characteristics consisting firm size and public accounting firm have a positive influence to voluntary disclosure, age of listings and liquidity have a negative influence to voluntary disclosure. Another variable that consists of leverage and profitability does not affect voluntary disclosure. For the second model, it has the result that extensive voluntary disclosures have a negative influence to cost of equity capital.